Competitive Capabilities, Operational Capabilities and Business Performance: A Study of Malaysia SMEs - Khatijah Omar, Maisarah Sebadak, Siti Nur ‘Atikah Zulkiffli, Siti Falindah Padlee, Juhaizi Mohd Yusof, (Opción, 2019)
The purpose of this paper is to investigate systematically the capabilities within SMEs in Terengganu, Malaysia. A survey was conducted among SMEs by using a questionnaire that was mailed to the owner. The empirical findings provide evidence that there is a relationship between competitive capabilities and business performance. However, there was no support for the hypothesis that operational capabilities have an impact on business performance. In conclusion, this examination of the level of competitive and operational capabilities among SMEs in Terengganu, Malaysia provides both researchers and managers with a greater understanding of these factors and their importance to business performance.